Pelatihan Pengolahan S. Cream Moera dalam Upaya Pencegahan Stunting dan Peningkatan Nilai Ekonomi Masyarakat di Desa Banjarsari - Rusminah Hs; Siti Ridayatul Husna; Busra Aulya; Rizky Meidiannisa Lukman; Lara Oktavia (Universitas Mataram, 2022)
Chronic nutrition resulting from insufficient nutrition and can cause disruptions for physical development, cognitive in children of a young age so that the ability to reasoning, thinking, and solving problems is lower than children growing in proper nutrition is understanding of stunting. The many benefits that come from extracting kelor leaves are a good idea and fit in as a nutritional supplement to young children. The levels of vitamins a, iron, potassium, proteins, kerbohydrate, vitamin c, and calcium (A Dudi Krisnadi, 2015) in kelor that provide a good nutritional supplement to children in growth and development.